Effect of Polydimethylsiloxane Oil Lubrication on the Friction of Cross-Country UHMWPE Ski Bases on Snow - Buene, Audun Formo; Auganæs, Sondre Bergtun; Klein-Paste, Alex (Frontiers in Sports and Active Living, 2022)
Silicone oils are known for their excellent lubricating properties, low toxicity and are ice-, snow- and hydrophobic. With the upcoming ban on fluorine-containing glide products imposed by the International Ski Federation (FIS), novel glide enhancers for skis are desperately needed. Here, the effect of four silicone oil viscosities (10, 20, 50 and 100 cSt) have been evaluated at three temperatures and snow conditions ranging from -10 °C dry snow to + 5 °C wet snow. In dry snow conditions, the shear forces introduced by the silicone oil film increased friction significantly compared to a ski without any treatment. On wet snow, the increased hydrophobicity from the silicone oils reduced the friction by 10%. While commercial glide wax outperformed the silicone oils, this study reports the silicone oils do have desirable friction reducing properties for wet conditions.